2023
DOI: 10.3390/microorganisms11112656
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Relative Abundance of Gut Bacteria Correlate with Lipid Profiles in Healthy Adults

Ineta Kalnina,
Dita Gudra,
Ivars Silamikelis
et al.

Abstract: The gut microbiome is a versatile system regulating numerous aspects of host metabolism. Among other traits, variations in the composition of gut microbial communities are related to blood lipid patterns and hyperlipidaemia, yet inconsistent association patterns exist. This study aims to assess the relationships between the composition of the gut microbiome and variations in lipid profiles among healthy adults. This study used data and samples from 23 adult participants of a previously conducted dietary interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…39 On the other hand, Massilistercora timonensis has an inverse correlation to the serum cholesterol, showing its potential in lipid regulation. 40 In summary, our study is the first to investigate and discuss the physiological function of curcuminoid degradants, FER and DFER, in HFD-induced obesity in a mouse model (Table 2).…”
Section: ■ Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…39 On the other hand, Massilistercora timonensis has an inverse correlation to the serum cholesterol, showing its potential in lipid regulation. 40 In summary, our study is the first to investigate and discuss the physiological function of curcuminoid degradants, FER and DFER, in HFD-induced obesity in a mouse model (Table 2).…”
Section: ■ Discussionmentioning
confidence: 95%
“…It was reported that the risk of disease caused by Streptococcus infection was found to increase in adults with obesity and diabetes . On the other hand, Massilistercora timonensis has an inverse correlation to the serum cholesterol, showing its potential in lipid regulation …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation